La judiciarisation des conflits linguistiques au Canada - Bilodeau, Roger (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
In this paper the author examines the importance of constitutional litigation as an instrument for promoting minority linguistic rights in Canada. He goes on to explain the reasons which drove him to challenge a unilingual English traffic summons which he received in Manitoba. Court proceedings are not the only means of strengthening minority language rights. The author underscores the importance of informing and educating the public as to the role and place of linguistic minorities in Canadian history. He also emphasizes the fact that heads of state should exercise more leadership in the area of language rights.